ANALYSIS OF THE EFFECTS OF OVERLOADING ON THE AGE OF THE TOLL ROAD CASE STUDY TANGERANG-MERAK KM 72 S/D KM 77 - Andri Irfan Hidayat; Raflo Barus (NAROTAMA UNIVERSITY, Indonesia, 2020)
Economic growth that occurred in Indonesia requires adequate infrastructure. A large number of infrastructure found in Indonesia is not accompanied by the compliance level of infrastructure users, the number of violations that occur causes a decrease in the life of a road. Overloading does not only causes road damage but also impacts the lack of road safety. Therefore, research and analysis are carried out to find out how much influence is given by the overload on a road, in this case, the age of the plan. The method used to find out how big the impact of a normal charge is with remaining life, which is to compare the age of a normal load plan with overload. By this method it is necessary to know the Vehicle Damage Factor (VDF) which will later be used to find the cumulative ESAL of each vehicle condition, then with the cumulative ESAL that occurs can know the remaining life of a road. From the conducted analysis result, it was found that each vehicle had an increase in vehicle damage factor (VDF), as well as the cumulative ESAL that was previously planned to receive cumulative ESAL in the amount of 20.602.172 with the cumulative overloading of ESAL, received to 284.426.068, due to the charge causing a decrease in remaining life is 4 years 9 months or decreased by 24%.